2016
DOI: 10.1155/2016/9289634
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Mucogingival Surgery with Free Gingival Autograft and Biomend Membrane and Coronally Advanced Flap in Treatment of Class III Millers Recession

Abstract: Introduction. Gingival recession is an apical shift of the gingival margin with exposure of the root surface. This migration of the marginal tissue leads to esthetic concerns, dentin hypersensitivity, root caries, and cervical wear. It is, paradoxically, a common finding in patients with a high standard of oral hygiene, as well as in periodontally untreated populations with poor oral hygiene. Changing the topography of the marginal soft tissue in order to facilitate plaque control is a common indication for ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Of the 16 articles focusing only on Miller class III GRs, nine of them [ 7 , 31 , 35 , 38 , 39 , 57 , 61 , 62 , 64 ] treated single GRs, six studies [ 6 , 53 , 56 , 58 60 ] included multiple GRs, and one study [ 67 ] included single or multiple Miller class III GRs. In the rest of articles, different kind of GRs were treated: single Miller class I, II and III GRs were treated in nine studies [ 40 , 41 , 44 , 48 , 50 , 51 , 63 , 65 , 66 ], whereas multiple Miller class I, II, III and IV GRs were treated in five articles [ 45 , 46 , 52 , 54 , 68 ], and single and multiple Miller class I, II and III GRs were treated in other seven articles [ 14 , 42 , 43 , 46 , 47 , 49 , 55 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 16 articles focusing only on Miller class III GRs, nine of them [ 7 , 31 , 35 , 38 , 39 , 57 , 61 , 62 , 64 ] treated single GRs, six studies [ 6 , 53 , 56 , 58 60 ] included multiple GRs, and one study [ 67 ] included single or multiple Miller class III GRs. In the rest of articles, different kind of GRs were treated: single Miller class I, II and III GRs were treated in nine studies [ 40 , 41 , 44 , 48 , 50 , 51 , 63 , 65 , 66 ], whereas multiple Miller class I, II, III and IV GRs were treated in five articles [ 45 , 46 , 52 , 54 , 68 ], and single and multiple Miller class I, II and III GRs were treated in other seven articles [ 14 , 42 , 43 , 46 , 47 , 49 , 55 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Graziani (2017) em sua pesquisa, mostraram que o tratamento periodontal cirúrgico se apresenta indicado em recessões maiores ou iguais a 5mm ou em locais com profundidade de sondagem maior ou igual a 6mm. Rath (2016) em seus trabalhos envolvendo cirurgia mucogengival em dois estágios com enxerto gengival livre no tratamento de recessões Classe III de Miller, obtiveram uma cobertura de 7 mm nas raízes e aumento de 4mm na gengiva Research, Society and Development, v. 10, n. 3, e51410313668, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i3.13668 inserida dos pacientes tratados seis meses após o tratamento. Enquanto Garces-Mcintyre (2017) em seus estudos prospectivos de retalhos coronais avançados combinados com enxerto de tecido conjuntivo para cobertura de recessões gengivais, tiveram como resultado uma cobertura média de 93,44% em todas as recessões tratadas e 65% dos casos tiveram uma cobertura completa.…”
Section: Resultsunclassified
“…demonstrated that two-stage procedure of FGG increases the success rate in the management of Millers Class I and II gingival recession. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…A case report on two-stage FGG showed a significant increase in WOKG and 7 mm of root coverage. [ 17 ] However, no study in our knowledge has been conducted previously for two-stage FGG techniques in Miller's Class III or IV recession apart from few case reports. [ 20 ] Furthermore, the mean root coverage in this study is quite appreciable, considering all the cases were Millers Class III or IV gingival recession (with fair to poor prognosis), further complicated by inadequate keratinized gingiva, which often has a poor success rate.…”
Section: Discussionmentioning
confidence: 99%